East-Central European and East European Neoclassicism as a Part of European Late Modernism - Foik, Melanie (Pitannâ lìteraturoznavstva, 2013)
Classicism in general, and the one of the 20th century in particular, are often characterized as a timeless and universal style and as a return to cultural tradition. Therefore it is considered to be a circular tendency in literature. The neoclassicism of the 1920s and 30s is often linked to the tradition of classicism. Although an undoubtedly important method to localize this phenomenon, such a linkage however leaves a number of questions unanswered. By taking an additional synchronous perspective of analysis (without losing the diachronic one) it is possible, to classify neoclassical tendencies as a distinct product of a certain epoch and, afterwards, to outline them at the intercept point of the two time axes. Synchronic consideration, however, entails the problem, that neoclassicism is neither a trend of classic modernism, nor a hovering counterbalance to avant-garde. As an appropriate solution to this problem one might resort to a four-membered model of modernist movement, which supplements the trichotomy of classic modernism – avant-garde – postmodernism with an additional paradigm of late modernism. In spite of all contingencies, a comparative analysis of neighboring East-European literatures from Poland, Russia and Ukraine allows to find basic common ground, which categorizes neoclassicism both as a general European phenomenon and as a part of European late modernism.